(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Human Resource Management faces the following challenges: a lack of an operational system. Because the School Management System Human Resources is not properly managed, it may supply incorrect information, causing increasing challenges in dealing with staff. Poor staff retention techniques. The lack of a good management strategy reduces the organization’s quality, which leads to employee exit and transfer to other firms. Lack of quality in recruiting, as well as inadequate recruitment strategy formulation, contribute to ignoring talented and knowledgeable job seekers. It is extremely difficult for the human resources department to communicate with other departments that are looking for new hires because of the department’s poor administration and slow system. The Human Resource Management System project will better deliver the information that HR personnel and school employees require. Every response offered to individuals participating in the School Management System Human Resources will be better structured and faster. Creating a strategy to acquire new personnel for the department and an efficient hiring procedure for talented individuals. Finding new workers with the appropriate talent will be easier with School Management, and every employee will receive the training they need to stay in their designated area. Maintaining a record of each employee’s information across the company is made simple by human resource management. The ability to oversee a more thorough human resource management strategy by being up to date on how each change inside the organization affects each employee. The system will aid the Department in maintaining and adhering to the Standard Operating Procedures when the head and staff of Human Resources need to turn over data, processes, and records in a hassle-free manner. It will also provide the best communication for a faster transaction without even needing more people to be involved. A secure database will be made available by the system to house files, data, and information that will be used for a long period.